THE EFFECT OF USING THE QUIZ TEAM ACTIVE LEARNING METHOD AGAINST STUDENT ACHIEVEMENT IN FIRST GRADE OF FIRST SEMESTER IN THE INTRODUCTION TO SOCIAL SCIENCES BASIC CONCEPTS OF SOCIAL SCIENCES CONCEPTS FOR THE ACADEMIC YEAR 2018/2019 - Stevani, Fruri; Fradani, Ayis Crusma (International Conference on Cultural Studies, 2019)
The purpose of this study was to determine the effect of the use of the quiz team's active learning methods on student achievement in the first grade of first semester in introductory social science courses on the basic concepts of social science in the academic year 2018/2019. The research method used in this study is the experimental method. The population in this study included IKIP PGRI Bojonegoro students at the first-level economic education department with a total of 70 students and the sampling technique in this study used cluster random sampling techniques. Data collection techniques in this study used the documentation and test methods. The analysis conducted in this study using the t test showed that = 1.715, with a large degree of freedom dk = 48 and a significance level ? = 5%. Obtained a price of 1,677. Thus rejected and accepted. This shows that there is an influence of the use of the active learning method of the quiz team type on the learning achievement of the first grade of first semester students in introductory social science courses on the basic concepts of social science in the academic year 2018/2019.